Transcriptomic and phenotype analysis revealed the role of rpoS in stress resistance and virulence of a novel ST3355 ESBL-producing hypervirulent Klebsiella pneumoniae isolate - Zhou, Yi; Cheng, Yue; Ma, Tianyou; Wang, Jun; Li, Shaoru; Wang, Jingdan; Han, Lei; Hou, Xinyao; Ma, Xinxin; Jiang, Sijin; Li, Pu; Lv, Jia; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction An extended-spectrum beta-lactamase (ESBL)-hypervirulent Klebsiella pneumoniae (HvKP) strain HKE9 was isolated from the blood in an outpatient. Methods The effect of the global regulatory factor RpoS on antimicrobial resistance, pathogenicity, and environmental adaptability was elucidated. Results HKE9 is a novel ST3355 (K20/O2a) hypervirulent strain with a positive string test and resistant to cephems except cefotetan. It has a genome size of 5.6M, including two plasmids. CTX-M-15 was found in plasmid 2, and only ompk37 was found in the chromosome. HKE9 could produce bacterial siderophores, and genes of enterobactin, yersiniabactin, aerobactin, and salmochelin have been retrieved in the genome. As a global regulatory factor, knockout of rpoS did not change antimicrobial resistance or hemolytic phenotype while increasing the virulence to Galleria mellonella larvae and showing higher viscosity. Moreover, rpoS knockout can increase bacterial competitiveness and cell adhesion ability. Interestingly, HKE9-M-rpoS decreased resistance to acidic pH, high osmotic pressure, heat shock, and ultraviolet and became sensitive to disinfectants (H2O2, alcohol, and sodium hypochlorite). Although there were 13 Type 6 secretion system (T6SS) core genes divided into two segments with tle1 between segments in the chromosome, transcriptomic analysis showed that rpoS negatively regulated T4SS located on plasmid 2, type 1, and type 3 fimbriae and positively regulate genes responsible for acidic response, hyperosmotic pressure, heat shock, oxidative stress, alcohol and hypochlorous acid metabolism, and quorum sensing. Discussion Here, this novel ST3355 ESBL-HvKP strain HKE9 may spread via various clonal types. The important regulation effect of rpoS is the enhanced tolerance and resistance to environmental stress and disinfectants, which may be at the cost of reducing virulence and regulated by T4SS.